KECUKUPAN ZAT GIZI DAN PERUBAHAN STATUS GIZI PASIEN SELAMA DIRAWAT DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR - Weta, I Wayan; Wirasamadi, NL Partiwi (PERSATUAN AHLI GIZI INDONESIA, 2009)
NUTRIENTS ADEQUACY AND CHANGES OF NUTRIRIONAL STATUS INDICES OF PATIENTS DURING HOSPITALIZED CARE IN CENTRAL GENERAL HOSPITAL OF SANGLAH DENPASARMalnourished in hospitalized patients was reported relatively high (30-50%). It was occurred duringhospital care (iatrogenic malnutrition). It was potentially decrease the curing process, prolong lengthof stay, and rose up the cost of care. A prospective study was conducted in General Central Hospitalof Sanglah Denpasar, included 42 male and female of hospitalized patients during period of February- Mart 2006 aged 18 to 70 years. The aim of the study was to assess the change of nutritional statusindex and nutrient adequacy of the subjects. The parameter of nutritional status (body weight andbody mass index) in the first and last day of care, average of food and nutrient intake duringhospitalized, estimate nutrient requirement and adequacy, was measured. The average length of staywas varied (6.5±5.25 days). The average macro nutrient intake of the subjects during hospitalizedwere less than the requirement level: energy (78%), protein (68%), carbohydrate (78%), but not in fat(99%). Macro nutrient adequacy in males were less than females subject. Indexes of nutritional statusdecreased; body weight (BW) (P 0.016), body mass index (BMI) (P0.019). It was higher decreasing inmales ( BW P0.029, BMI P0.027) than females (BW and BMI P0.05). In conclusion, decreasing ofnutritional status of patients was occurred in hospitalized patients. The adequacy of nutrient intakewas lower than the requirement level. There are a complex nutritional problems in hospitalizedpatients. Nutritional service should be performed comprehensively in order to maintain nutritionalstatus and increase curing process of the patients. It should be performed systematically andintegrated through the team approach, which is play role in (1) define the diagnosis in term of clinical,biochemical, and nutritional status, (2) measure nutrient requirement and decide the feeding method,(3) carry out the nutritional support intervention, and (4) undertake the monitoring and evaluating asan impact of intervention.Keywords: Hospitalized patients, Hospital of Sanglah, index of nutritional status, nutrientadequacy.